The distress premium puzzle - Ali K. Ozdagli (Federal Reserve Bank of Boston, 2010)
Fama and French (1992) suggest that the positive value premium results from risk of financial distress. However, recent empirical research has found that financially distressed firms have lower stock returns, using empirical estimates of default probabilities. This paper reconciles the positive value premium and the negative distress premium in a model that decouples actual and risk-neutral default probabilities. Moreover, in agreement with the data, firms with higher bond yields have higher stock returns in the model. The model also captures the fact that book-to-market value dominates financial leverage in explaining stock returns. Finally, the model predicts that firms with higher risk-neutral default probabilities should have higher stock returns, a hypothesis that can be tested using credit default swap premiums.
Keywords: G12; G32; G33; 330